Prinsip Pendidikan Karakter dalam Islam: Studi Komparasi Pemikiran Al-Ghazali dan Burhanuddin Al-Zarnuji - Setiawan, Agus (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
The implementation of character education that is done by the Indonesian government recently has been provoked by al-Ghazali and Burhanuddin al-Zarnuji long ago. It was proven by some written thoughts of al-Ghazali and Burhanuddin al-Zarnuji. They were very famous scientists in their era and widely welknown as educational experts who produced some phenomenal thoughts many people use today. Al-Ghazali and Burhanuddin al-Zarnuji lived in the era of Bani Abbasiyah monarchy, but Both of them lived in different era. Al-Ghazali was born first, then Burhanuddin al-Zarnuji. They had different mazhab, al-Ghazali went to the traditional principle of mazhab Syafi’I and Burhanuddin al-Zarnuji went to the modern principle of mazhab Hanafi. The differences, of course, would create a different thought. Still, they might have a similar principle of Islamic character education. The thoughts of character education of al-Ghazali have been poured in the “Ayyuha Walad” focusing to the students’ character building characterized by religiously obedient, skillfull of general and religious knowledge, socially helpful, affectionate, generous, good citizen, and coloring the society. Some applicable thoughts of character education of Ayyuha al-Walad of al-Gazhali to the contemporary education are: the balance of the happiness purposes of the recent life and the life after death, qana’ah and tawakal, affectionate, caring other, patience, honesty, philanthrophy, social works, generousity, democratic, peace makers, and patriotic. Those characters are also directed in the islamic character education nowdays. So that, the thoughts of al-Ghazali positively and responsively are absorbed by the Indonesian government to build the national character widely implementing in the national curriculum based on the local wisdom and the Islamic values. In the end, the students are able to live happily based on the Islamic rules by implementing the good behavior. Similar to the al-Ghazali’s thought, Burhanuddin al-Zarnuji, in “Ta’lim al-Muta’alim”, wrote some important principles of character building consists of the phisycal and inner values in education.